A systematic literature review on the development of STEM-based module - Rido Illah; Eko Susetyarini (Universitas Muhammadiyah Malang, 2024)
Along with the growing awareness of the importance of STEM education, various research regarding STEM is increasingly being carried out. However, educators still have difficulty getting complete and comprehensive information regarding STEM modules that have been developed by researchers that can be applied in the classroom. The aim of this systematic literature review is to analyze papers that develop STEM-based modules with two review focuses, namely (1) the development model used; and (2) validation results of the modules that have been developed. The papers reviewed were limited to research published from 2019 using 2023 and accredited SINTA 2 and 3. Search results obtained 10 articles reporting the development of STEM-based modules. The most frequently used development model is ADDIE. This SLR provides a comprehensive analysis of the current trend of STEM education module development and be able to encourage future researchers to explore other aspects of STEM for research.